Acu‐URO17 is a highly sensitive and specific bladder cancer biomarker - Liwu Guo; Alexandra Cid; John Cucci; Brian Kunkel; Lisa Defeis; Michael Matthews (BJUI Compass)
Abstract Objective This study evaluates the efficacy of Acu‐URO17, a highly sensitive and specific immunocytochemistry (ICC) test targeting Keratin 17, in comparison to urine cytology and UroVysion™ fluorescence in situ hybridization (FISH) for detecting bladder cancer cells in voided urine specimens. Methods Acupath conducted a large‐scale comparison study using 2378 voided urine specimens. Acu‐URO17, urine cytology and UroVysion™ FISH were performed on these specimens according to standardized protocols. Sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated for Acu‐URO17 in comparison to urine cytology and UroVysion™ FISH. Results In cases diagnosed with high‐grade urothelial cancer via urine cytology, Acu‐URO17 demonstrated a sensitivity of 96% and a specificity of 82%. When compared to UroVysion™ FISH results, Acu‐URO17 exhibited a sensitivity of 97.1% and a specificity of 77.8%, surpassing the sensitivity of UroVysion™ FISH (57.1%). Notably, Acu‐URO17 showed a high NPV of 99.9%, indicating its reliability in confirming negative urine cytology results and risk‐stratifying atypical and suspicious cytology results. Conclusion The results of this large‐scale prospective study support Acu‐URO17 as a clinically relevant, non‐invasive and cost‐effective tool for detecting bladder cancer cells in voided urine specimens. Its high sensitivity, specificity and NPV make it a valuable adjunct to urine cytology and UroVysion™ FISH in the diagnosis and management of urothelial carcinoma (UC).